Mapeamento da pesquisa acadêmica brasileira sobre Geometria Espacial: período 2007 a 2017 - Sanchez, Jéssica Barbosa dos Passos (2018)
The objective of this research was to map, describe, analyze, discuss thematic trends and theoretical-methodologies in the field of Spatial Geometry. In this way, we made systematically cut-outs in Brazilian researches, produced in the period from 2007 to 2017, in strict sense graduate programs in Mathematics Education. We use a state-of-the-art methodology step called mapping. The data were selected from the search of academic productions in the Bank of Thesis and Dissertations of CAPES. We identified 11 academic masters and 3 doctoral theses related to our mathematical object: Spatial Geometry. The topics developed in the selected researches were: metric geometry, regular polyhedral, prisms (triangular and quadrangular bases), pyramids, cylinders, cones and spheres, including elements of these solids, surface area, surface planning and volume measurement, we conclude that the themes did not change during the studied period, because we did not find any research reflected in the curricular structure. To do so, we created three axes of analysis: The first axis refers to the analysis of the works by which they used games, manipulative materials and non-digital resources; in the second axis we analyze the researches, whose objective was the resources of information technology and communication (ICT) and, in the last axis, since they deal with strategies for the teaching of spatial geometry. We conclude, among the three axes - the predominance of investigations in high school. Although, we obtained the highest concentration of works in the second axis, to the detriment of the first and third, evidencing a tendency of change in the teaching strategies, whose consequence was the use of digital technologies